PRE-SEQUENCES AND SPEECH ACTS IN CEBUANO RADIO HEALTH COMMERCIALS IN CEBU CITY - Ceska Marie R Apalla; Keeshia Joy S San Juan; Rowanne Marie R Maxilom (Kajian Linguistik dan Sastra, 2017)
This research attempted to identify and analyze the Cebuano-Bisaya radio health commercials using Schegloff’s (2007) framework on pre-sequences with the support of Yule’s (1996) speech act theory. Thirty (30) Cebuano-Bisaya radio health commercials were gathered from two selected radio stations. The results revealed that representatives were the most dominant function in speech acts that reflected in pre-sequences specifically with pre-offers and pre-announcements through  drama  and  testimonial  categories  which  are  often  used  in  medicinal product  commercials.  In  advertising  strategies,  Cebuano-Bisaya  commercials use  Representatives  and  Expressive  as  persuasive  devices  in  addressing  the advertisers’ intended  message  to  the  target  audience.  Also,  Cebuano-Bisaya commercials used Representatives and Expressive as an appeal to suggest an intention for the listener to buy advertised products.Keywords: Cebuano, commercial, health, pre-sequences, radio, speech acts